Intensified DES mediated ultrasound extraction of tannic acid from onion peel - Sukor, N. F.; Selvam, V. Panner; Jusoh, Rohayu; Kamarudin, N. S.; Abd Rahim, Syarifah (Elsevier Ltd, 2021)
Ultrasound–assisted extraction using deep eutectic solvent (DES) was performed to extract tannic acid from onion peel. Notably, DES is an excellent extraction agent, which yielded 641.16 ± 0.01 μg/g of tannic acid compared to the extraction using a conventional solvent (368.99 ± 0.02 μg/g). Subsequently, the research was conducted based on several exploited parameters and achieved the highest extraction yield (1705.79 ± 0.01 μg/g) at the DES ratio of 1:1 (mass ratio of choline chloride to urea), solid to solvent ratio of 1:10 and duty cycle of 10%. The onion sample exhibited higher antioxidant capacity than standard ascorbic acid, which was expressed in the lower values of the half-maximal inhibitory concentration (IC50) at 7.70 ± 1.12 and 10.14 ± 0.11 mg/ml, respectively. Moreover, the Fick's model successfully forecasted that diffusivity is the controlling factor in the extraction of tannic acid via the DES mediated ultrasound–assisted extraction method.